Associations Among Behavioral Sleep Disturbance, Family Functioning, and Controller Medication Adherence in Children with Asthma. Issue 3 (April 2017) - Sonney, Jennifer T.; Segrin, Chris; Ward, Teresa M.
ABSTRACT: Objective: This study examined the associations among child sleep disturbances, family functioning, and asthma controller medication adherence in school-age children with persistent asthma. Methods: Thirty-four children aged 6 to 11 years and a parent independently reported on asthma control and controller medication adherence. Parents also reported on family functioning (behavior control) and child sleep disturbances (bedtime resistance, daytime sleepiness). Hierarchical linear regression models tested sleep disturbance variables as predictors of family functioning and medication adherence. A mediation model tested behavior control as a mediator between sleep disturbance and medication adherence. Results: Seventy-nine percent of the children had well-controlled asthma. Despite a mean of 9.48 hours of child sleep per night, 73% of the children had clinically significant disturbed sleep. Controlling for child age, bedtime resistance accounted for 32% of the variance in family behavior control ( F (1, 31) = 14.75, p < .01). Behavior control also significantly mediated the relationship between total sleep disturbance and medication adherence, with a standardized indirect effect of β = −.17 (95% confidence interval [CI], −.47 to −.03) for parent-reported adherence and β = −.12 (95% CI, −.36 to −.01) for child-reported adherence. Conclusion: Child behavioral sleep disturbances significantly predicted family behavior control. Although child sleep disturbances did not significantly predict asthma controller medication adherence, there was a significant indirect effect of sleep disturbance on medication adherence through compromised family behavior control. Developmentally appropriate behavioral sleep interventions may improve family functioning and child asthma controller medication adherence. Family functioning may also be an entry point for intervention to improve medication adherence.